Enterobius vermicularis infestation causing terminal ileal gangrene - Rizwan, Mohamed; Raju, Mithun; George, Rupesh (International Surgery Journal, 2021)
Enterobius vermicularis is one of the most common nematode infestations seen worldwide. This condition is commonly seen in children. Although asymptomatic, they present with symptoms of perianal itching commonly at night with perianal excoriations. In this case report we present a case 79 years old man with multiple co-morbidities who presented with non-bilious vomiting and severe abdominal pain. Emergency laparotomy was performed during which terminal ileal gangrene was noted. Ileo-caecal wall revealed multiple parasites (enterobius).